2017
DOI: 10.1080/02699931.2017.1358698
|View full text |Cite
|
Sign up to set email alerts
|

Using temporal distancing to regulate emotion in adolescence: modulation by reactive aggression

Abstract: Adopting a temporally distant perspective on stressors reduces distress in adults. Here we investigate whether the extent to which individuals project themselves into the future influences distancing efficacy. We also examined modulating effects of age across adolescence and reactive aggression: factors associated with reduced future-thinking and poor emotion regulation. Participants (N = 83, aged 12-22) read scenarios and rated negative affect when adopting a distant-future perspective, near-future perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 68 publications
8
64
4
Order By: Relevance
“…This study confirmed that temporal distancing can be an effective emotion regulation strategy when presented with hypothetical but age-appropriate and moderately distressing scenarios. In addition, adopting a distant-future perspective was more effective at alleviating distress than adopting a near-future perspective, in line with Ahmed et al (2018) and Bruehlman-Senecal and Ayduk (2015). This finding suggests that temporal extent is a key factor in temporal distancing efficacy as opposed to more general cognitive processes associated with imagining any future time point (although we acknowledge that the present study is unable to elucidate the precise mechanism by which distance exerts its salutary effects).…”
Section: Temporal Distancing Attenuates Ratings Of Distresssupporting
confidence: 65%
See 2 more Smart Citations
“…This study confirmed that temporal distancing can be an effective emotion regulation strategy when presented with hypothetical but age-appropriate and moderately distressing scenarios. In addition, adopting a distant-future perspective was more effective at alleviating distress than adopting a near-future perspective, in line with Ahmed et al (2018) and Bruehlman-Senecal and Ayduk (2015). This finding suggests that temporal extent is a key factor in temporal distancing efficacy as opposed to more general cognitive processes associated with imagining any future time point (although we acknowledge that the present study is unable to elucidate the precise mechanism by which distance exerts its salutary effects).…”
Section: Temporal Distancing Attenuates Ratings Of Distresssupporting
confidence: 65%
“…Third, response options were nine schematic faces ranging from frowning to smiling, rather than numbers. Finally, we asked participants to rate distance in time adopted for the distantfuture condition only once at the end of the experiment, while Ahmed et al (2018) asked this question after every distant-future and near-future trial. These changes were necessary to reduce the length of the experimental session and maintain engagement of younger participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A distant perspective can be achieved in multiple ways. For example, one can envision the event through the eyes of a spatially distanced self (i.e., “spatial distancing”; Ayduk & Kross, ; Kross, Gard, Deldin, Clifton, & Ayduk, ; White, Kross, & Duckworth, ) or through the eyes of a future self (i.e., “temporal distancing”; Ahmed, Somerville, & Sebastian, ; Bruehlman‐Senecal & Ayduk, ; Bruehlman‐Senecal et al, ).…”
Section: Self‐distanced Meaning Making and Milmentioning
confidence: 99%
“…The journal has always operated at the crossroads of multiple disciplines, and this remains true in the present day and age. Indeed, a mere glance at the ten most down-loaded articles during 2018 features articles from developmental psychology (Ahmed, Somerville, & Sebastian, 2018;Kret, 2018;Lennarz, Lichtwarck-Aschoff, Timmerman, & Granic, 2018), social psychology (Hopkins et al, 2016;van Osch, Zeelenberg, & Breugelmans, 2018), and clinical psychology (Slofstra et al, 2018). In addition, there were trans-disciplinary articles on embodiment of emotion (Bernstein & McNally, 2017;Veenstra, Schneider, & Koole, 2017) and our brief review of the history of Cognition & Emotion (Rothermund & Koole, 2018).…”
Section: Cognition and Emotion In 2018mentioning
confidence: 99%